2012
DOI: 10.1161/strokeaha.111.647271
|View full text |Cite
|
Sign up to set email alerts
|

Silent Infarcts and Cerebral Microbleeds Modify the Associations of White Matter Lesions With Gait and Postural Stability

Abstract: Background and Purpose— Although cerebral white matter lesions (WMLs), silent infarcts (SIs), and microbleeds (MBs) are individually associated with poorer gait and balance, it is unknown if they interact. We studied the interactions of WML volume with SI and MB on gait and postural stability. Methods— Participants in a population-based study aged 60 to 86 years underwent brain MRI, computerized gait measurement, and a physiological profile assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 26 publications
1
67
0
Order By: Relevance
“…CMHs have also been shown to be associated with gait dysfunction both in humans (Choi et al ., 2012) and experimental animals. Importantly, we also revealed that increased incidence of CMHs leads to progressive gait abnormalities in IGF‐1‐deficient mice mimicking the phenotype observed in hypertensive aged mice (Toth et al ., 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…CMHs have also been shown to be associated with gait dysfunction both in humans (Choi et al ., 2012) and experimental animals. Importantly, we also revealed that increased incidence of CMHs leads to progressive gait abnormalities in IGF‐1‐deficient mice mimicking the phenotype observed in hypertensive aged mice (Toth et al ., 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Both cognition and gait impairments are associated with lower grey (Rosano et al 2007;Jokinen et al 2012;Callisaya et al 2014) and white matter volume (Callisaya et al 2013), as well as cerebrovascular disease such as white matter hyperintensities (Jokinen et al 2012) and cortical and subcortical infarcts (Rosano et al 2006;Choi. 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2012). Cerebrovascular disease and brain atrophy, particularly in prefrontal and subcortical areas, may underlie the associations between non-amnestic MCI and slower FWS (Rosano et al 2007;Choi et al 2012;Callisaya et al 2014). Associations between brain imaging markers and FWS have not been undertaken, but it could be hypothesised that walking at a fast speed might require greater areas of cerebral brain activation to perform the challenging task.…”
Section: Discussionmentioning
confidence: 99%
“…Lacunes are known to be associated with stroke and gait disturbance in elderly individuals (9293). Furthermore, patients with AD are more likely to have lacunes on MRI than individuals without dementia (7794).…”
Section: Structural Imagingmentioning
confidence: 99%